An Analysis of the Concepts of the Religious and the Secular in the Thought of Paul Tillich - Porter, Bruce C. (My University, 1971)
The thesis aims to analyze the thought of Paul Tillich with a view to finding out the meaning and meaningfulness of his understanding of the religious and the secular. Specifically, this has been done through three steps: (1) by an analysis of Tillich's notion of the secular in terms of variations of his broad definition of religion; (2) by a look at the secular in its strongest cultural expression - autonomous culture; and (3) by a discussion of the chief sources of confusion and disagreement in his views of the religious and the secular. The thesis concludes with the author's views on the extent to which problems surrounding Tillich's broad definition of religion do, or do not, undercut the meaningfulness of that definition.
Keywords: Religion; Religion